The impact of the Belt and Road Initiative on Central Asia - Indeo, Fabio (Henry Stewart Talks, 2019)
Geopolitics, Belt and road initiative (BRI), BRI structure, Economic corridors, Trade & energy import routes, Multi-vector foreign policy, Security, Central Asia-China pipeline